2011
DOI: 10.1002/pat.1747
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of clay nano‐biocomposites based on poly(lactic acid) plasticized with polyadipates

Abstract: The use of nano‐biocomposites based on plasticized poly(lactic acid) (PLA) has been proposed as a way to improve the polymer ductility and to expand PLA applications window. Novative nano‐biocomposites were elaborated with PLA plasticized by polyadipates (15 wt%) with different molar masses (from 1500 to 2500 Da), with 2.1 wt% of an organo‐modified montmorillonite (O‐MMT). These materials showed enhanced ductility and barrier properties. The clay was swelled in liquid polyadipates prior to their blending with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 42 publications
4
45
0
1
Order By: Relevance
“…Accordingly, the OIt measurements did not show any benefit stemming from LDH (PLA_LDH) and its dispersion (PLA_(LDH-PLACOO)_1 and PLA_(LDH-PLA-COO)_2) (see Table 2). Instead, the addition of MMT-PLANH 3 , even if seemingly does not improve the thermal performance of the PLA matrix, as already reported in literature for PLA-based composites with MMT clays having similar morphologies [18,22,31], preserved the thermal stability of the PLA and showed a significant effect onto the OIT results. In particular, with reference to nanocomposites obtained by commercial organophilic MMT, Wu et al [32] reported even a decrease in the stability and Nieddu et al [33] fluctuating results depending on the content of inorganic clay and presumably on the morphology.…”
Section: Resultssupporting
confidence: 63%
“…Accordingly, the OIt measurements did not show any benefit stemming from LDH (PLA_LDH) and its dispersion (PLA_(LDH-PLACOO)_1 and PLA_(LDH-PLA-COO)_2) (see Table 2). Instead, the addition of MMT-PLANH 3 , even if seemingly does not improve the thermal performance of the PLA matrix, as already reported in literature for PLA-based composites with MMT clays having similar morphologies [18,22,31], preserved the thermal stability of the PLA and showed a significant effect onto the OIT results. In particular, with reference to nanocomposites obtained by commercial organophilic MMT, Wu et al [32] reported even a decrease in the stability and Nieddu et al [33] fluctuating results depending on the content of inorganic clay and presumably on the morphology.…”
Section: Resultssupporting
confidence: 63%
“…PLA has been used intensively in food and industrial packaging [4]. Surprisingly, PLA has the potential to replace conventional petroleum-based plastics such as polystyrene, polyethylene, polypropylene, polyethylene terephthalate in many disposable or short-term applications [5].Naturally, PLA has a good mechanical properties such as high strength, high Young modulus, and high biocompatibility [6].However, PLA has some drawbacks such as its ductility at ambient temperature. To improveits intrinsic properties, blending is applied using other polymer such as some plasticizers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polylactide (PLA) is one of the most promising bio-based polyester for food packaging [1,2] because of its good mechanical, superior transparency, ease of processing and availability in the market [3]. In this sense, poly(lactic acid) (PLA) is one of the most attractive biopolymers with many short-term or disposable applications, such as disposable cutlery (plates, cups, lids and drinking straws), bags and film packaging [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…PLA is also widely used in rigid and flexible food packaging applications [6] since it has been approved by the US Food and Drug Administration (FDA) as a food contact substance [7,8].. However, the use of PLA for food packaging is somewhat limited because of its poor ductility, thermal and oxygen barrier properties [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation